The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9051291
|View full text |Cite
|
Sign up to set email alerts
|

Visual Feedback and Postural Control in Multiple Sclerosis

Abstract: As people with multiple sclerosis (pwMS) manifest heterogeneous demyelinating lesions that could affect somatosensory or vestibular ways, visual stimulus as feedback could be especially relevant to achieve postural control. This has clinical importance for the development of preventive measures and rehabilitation therapies in order to avoid falls and accidents in this group. In our study, we objectively evaluated the influence of visual feedback on the stabilization of balance in pwMS versus healthy controls (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 35 publications
1
24
0
2
Order By: Relevance
“…Using a treadmill integrated system, Kalron et al found that minimally impaired pwMS chose a slower jogging tempo, with wider steps and higher double support time, which might be attributed to a safety strategy (Kalron et al, 2013). In balance assessment, a recent study suggested a high sensitivity of the range of the sway area from the patient's center of gravity as well as of the average speed, to uncover early balance deficits in pwMS not detectable for the physician (Inojosa et al, 2020b). Regarding a risk-of-fall screening, balance outcomes measured by force platforms showed better discriminative properties compared to the Berg Balance Score (Prosperini et al, 2013).…”
Section: Sensor Floor Platesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a treadmill integrated system, Kalron et al found that minimally impaired pwMS chose a slower jogging tempo, with wider steps and higher double support time, which might be attributed to a safety strategy (Kalron et al, 2013). In balance assessment, a recent study suggested a high sensitivity of the range of the sway area from the patient's center of gravity as well as of the average speed, to uncover early balance deficits in pwMS not detectable for the physician (Inojosa et al, 2020b). Regarding a risk-of-fall screening, balance outcomes measured by force platforms showed better discriminative properties compared to the Berg Balance Score (Prosperini et al, 2013).…”
Section: Sensor Floor Platesmentioning
confidence: 99%
“…For balance testing, the Romberg test is used to evaluate variations of the body while standing on a flat surface with the feet hip-wide and parallel to each other (Inojosa et al, 2020b). For comparing the stability, the test is performed with open and closed eyes (Inojosa et al, 2020c).…”
Section: Assessment Of Balancementioning
confidence: 99%
See 1 more Smart Citation
“…visual or sensory) and results of the cerebrospinal fluid analysis ( Doshi and Chataway, 2016 ; Deangelis and Miller 2014 ). Also, the static posturography revealed to be valuable in the MS clinic, particularly in the diagnosis of motor dysfunctions related to falls ( Boes et al, 2012 ; Cameron and Lord, 2010 ; Inojosa et al, 2020a , b ; Kalron et al, 2016a , b ; Nilsagård et al, 2009 ; Pau et al, 2017 ; Prosperini et al, 2013 ; Prosperini and Castelli, 2018 ) Simplicity and safety of static posturographic tests make it attractive for use in the neurological clinic. Additionally, static posturography seems very sensitive to every change within the sensory-motor system which may be of key importance in the diagnosis and monitoring of MS (for review see Prosperini and Castelli, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the diagnostic value of static posturography has been proved in the aging of the nervous system, and motor disorders and injuries. Recently, substantial research efforts focus on MS ( Wajda et al, 2016 ; Prosperini et al, 2013 ; Inojosa et al, 2020a , b ; Kalron et al, 2016a , b ) Continuing this line of research we focused here on sway characteristics in MS. Multiple sclerosis signs and symptoms may differ greatly from patient to patient and throughout the disease depending on the location of affected nerve fibers.…”
Section: Introductionmentioning
confidence: 99%